Obraz polityków rosyjskich na łamach tygodników „Wprost”, „Polityka”, „Newsweek” - Patocka-Sigłowy, Urszula (Przegląd Rusycystyczny, 2012)
Urszula Patocka-Sigłowy Uniwersytet Gdański, Gdańsk, Poland PRZ.RUS@op.pl ОБРАЗ РУССКИХ ПОЛИТИКОВ НА СТРАНИЦАХ ЕЖЕНЕДEЛЬНИКОВ „WPROST”, „POLITYKA”, „NEWSWEEK” Резюме Представленный в статьях еженедeльников „Wprost”, „Polityka”, „Newsweek” образ русских политиков не является для них положительным. На страницах журналов Россия показана, как страна, в которой властвуют абсолютные правители — царь Владимир Путин и его наследник Дмитрий Медведев. Как они, так и представители политической элиты лишены моральных принципов. Они считают, что в политике самое главное это собственная выгода. изменения на посту президента не внесли ничего нового в политическую систему России. THE IMAGE OF RUSSIAN POLITICIANS IN CHOSEN ISSUES OF WEEKLY MAGAZINES „WPROST”, „POLITYKA”, „NEWSWEEK” Summary The image of Russian politicians in articles published in “Wprost”, “Polityka”, “New-sweek” is not positive. Russia is a country ruled by an absolute monarch — tsar Vladimir Putin and his successor Dmity Medvedev. They and the representatives of political elites are deprived of ethical principles. According to them, only personal profit counts and the best effects are brought by policy based on blackmail. Moreover, the change of the president did not bring anything new to the quality of political system.